Treatment of recalcitrant wife in Islamic law: the need for a purposive juridical construct - Haneef, Sayed Sikandar Shah (De Gruyter, 2012)
Islamic law dealing with the issue of the scriptural treatment of a recalcitrant wife (nushuz) as detailed by both exegetes and classicaljurists has emerged as one of the much debated topics in readings on Muslim women in our time. Some go the feminist way; others tend to be reformists while the vast majority remain traditionalists, konically, however, all these advocates, by and large, have one thing in common, namely they are locked in the traditional literal methodology of legal construction. This snrdy, however, calls for taking the discourse beyond the confines of literalistic polemics to that of purposive methodology and analytical legislative constructs. It concludes that the three-stage procedures of disciplining a recalcitrant wife as legislated by the Qur'an, is intended to mitigate the harsh treatment of such wives in socio-cultural conditions in which wife-battering was normal. To literally adopt such a procedure for restoring the relationship of marriage at present time instead of repairing marital discord, will further ruptures it; thus it is against the end-goal ofthe law on nushuz.